Resident Workshop Standardizes Patient Handoff and Improves Quality, Confidence, and Knowledge. Issue 9 (September 2017) - Murphy, Heidi J.; Karpinski, Aryn C.; Messer, Amanda; Gallois, Julie; Mims, Michelle; Farge, Ashley; Hernandez, Lauren; Steinhardt, Michelle; Sandlin, Chelsey
Abstract : Objectives: Residency programs are required to instruct residents in handoff; however, a handoff curriculum endorsed by the Accreditation Council for Graduate Medical Education does not exist. Although curricula are available, we preferred to use a curriculum that could be taught quickly, was easy to implement, and used a mnemonic that resembled current practices at our institution. We designed and implemented a novel handoff educational workshop intended to improve resident confidence and performance. Methods: In this observational study, pediatric residents across postgraduate training years during winter 2014–spring 2015 participated in two study segments: a handoff workshop with questionnaires and handoff observations. Co-investigators developed and led an interactive workshop for residents that emphasized a standardized approach using the SIGNOUT mnemonic (see text for definition). The effect of workshop participation on handoff abilities was evaluated using a validated, handoff evaluation tool administered before and after the workshop. Qualitative feedback was obtained from residents using pre- and postworkshop surveys. Results: Forty-three residents participated in the workshop; 41 residents completed handoff observations. Improvements were noted in clinical judgment ( P = 0.02) and organization/communication ( P = 0.005). Pre- and postworkshop surveys demonstrated self-perceived increases in confidence, comfort, and knowledge ( P < 0.001). Conclusions: Improvements in handoffs, particularly in clinical judgment and organization/communication domains, suggest that a more standardized handoff approach is beneficial, especially for postgraduate year 1 residents. The novel, interactive workshop we developed can be taught quickly, is easy to implement, is appropriate for all resident training levels, and improves resident confidence and skill. This workshop can be implemented by training programs across all disciplines, possibly leading to improved patient safety. Abstract : Although residency programs are required by governing bodies such as the Accreditation Council for Graduate Medical Education to instruct residents in patient handoff, an endorsed curriculum does not exist. Even though patient handoff curriculums are available in the literature, many require multiple hours for resident training and recommend a handoff format that is different from the format in use at the authors' institution. The authors designed and implemented a novel handoff educational workshop that could be taught quickly, was easy to implement, and used a memory mnemonic to improve resident handoff confidence and performance.